Productivity of Indigofera zollingeriana under different canopy and soil acidity level in oil palm estate - Iwan Herdiawan (Jurnal Ilmu Ternak dan Veteriner, 2016)
Oil palm estate area in Indonesia is generally located in a sub-optimal land that has great opportunity for the development of forage supply. This study aims were to determine productivity of Indigofera zollingeriana under various canopy level. This research used factorial randomized block design with 3 canopy levels (under 2, 5, and 7 year oil palm canopy) and 2 levels of soil acidity (neutral and acid soil) treatments, where each treatment was repeated 4 times. Parameters observed were production and nutrient content of Indigofera zollingeriana. Research results showed that there was no interaction between the canopy levels and soil acidity on the production of fresh leaves, stems/branches, biomass, and leaves/stem ratio of I. zollingeriana. Production of fresh leaves, stems, biomass, and leaves/branches ratio of I. zollingeriana significantly (P <0.01) decreased along with increase of canopy level. Soil acidity significantly (P <0.05) decreased production of fresh leaves, stems, biomass, and leaves/branches ratio. Level of canopy treatment significantly (P <0.05) increased content of crude protein, crude fiber and energy, otherwise value of in vitro dry matter digestibility (IVDMD) and organic matter digestibilyity (IVOMD) were decrease. Soil acidity significantly (P <0.05) decreased calcium content, in vitro dry matter digestibility (IVDMD) and organic matter digestibility (IVOMD) of I. zollingeriana.